The Analysis of Student’s Writing By Using Systemic Functional Grammar - Fauziah, Fauziah; Ramlan, Ramlan (Universitas Malikussaleh, 2020)
This study is discussed about an analysis of a review text entitled Leonardo Da Vinci written by one of first grade student of a senior high school in Bandung. It consists of three parts: introduction, discussion and conclusion. The introduction describes the lexicogrammatical features of student’s Review text. The discussion provides the analysis of Theme system, Transitivity system, Modality and Grammatical metaphor by using Systemic Functional Grammar. Finally, the conclusion sums up the result of the analysis and briefly explains implication of the topic. He organized the text successfully that achieved the purpose, generic structure and linguistic feature of review text in general.